Analisis Paulus Menjadi Rasul Allah Menurut Galatia 1:15-17: Rencana Allah yang Tersembunyi - Maritaisi Hia (Institut Agama Kristen Negeri Palangka Raya, 2023)
This article is an analysis of Paul becoming God's apostle according to Galatians 1:15-17. The office of an apostle is a position that comes from God, in which God reveals His Gospel to the people He has chosen. God chooses someone to be His apostle to preach the truth of the Gospel to everyone. Paul is a person who has been chosen by God since he was in the womb to become an apostle of God who will preach the Gospel. However, some views that interpret Paul's apostleship only look at it from the side of God's calling or see it from the side of Paul's repentance. For this reason, the writer conducted research on the text of Galatians 1:15-17 by using a qualitative research method that uses the exegesis method of 4 layers of Bible meaning. The four layers are Layer I Historia/Sarkic Layer II (Theoria/Noetic/spiritual meaning). Layer III (Psychic/moral). And layer IV (Anagogic/Eschatology). So through that it gives research results that Paul who was chosen by God to be an Apostle and called him to preach the Gospel was God's hidden plan for a real/divine purpose. Where in it has wrapped how Paul was chosen and called by God and also his repentance. God's plan is said to be hidden because no one knows God's plan except the heart that is given to God and wants to listen to His call. Artikel ini adalah sebuah analisis tentang Paulus menjadi rasul Allah menurut Galatia 1:15-17. Jabatan seorang rasul adalah jabatan yang berasal dari Allah, dimana Allah mewahyukan Injil-Nya kepada orang yang telah Ia pilih. Allah memilih seseorang menjadi rasul-Nya untuk memberitakan kebenaran Injil kepada semua orang. Paulus adalah orang yang telah dipilih Allah sejak dalam kandungan untuk menjadi seorang rasul Allah yang akan memberitakan Injil. Akan tetapi beberapa pandangan yang menafsir tentang kerasulan Paulus hanya melihat dari sisi panggilan Allah atau melihat dari sisi pertobatan Paulus saja. Untuk itu penulis melakukan penelitian di dalam teks Galatia 1:15-17 dengan memakai metode penelitian kualitatif yang menggunakan metode eksegesis 4 lapisan makna Alkitab. Keempat lapisan tersebut yakni, Lapisan I Historia/Sarkic Lapisan II (Theoria/Noetic/spiritual meaning). Lapisan III (Psychic/moral). Dan lapisan IV (Anagogic/Eskatologi). Sehingga melalui itu memberikan hasil penelitian bahwa Paulus yang dipilih Allah menjadi Rasul dan memanggilnya untuk memberitakan Injil adalah rencana Allah yang tersembunyi untuk tujuan yang nyata/ilahi. Dimana di dalamnya telah membungkus bagaimana Paulus dipilih dan dipanggil oleh Allah dan juga pertobatannya. Rencana Allah dikatakann tersembunyi karena tidak ada seorangpun yang mengetahui rencana Allah kecuali hati yang diberikan kepada Allah dan mau mendengarkan panggilan-Nya.